Google and the digital divide : the bias of online knowledge - Segev, Elad. (Oxford : Chandos Pub., 2010)
Aimed at information and communication professionals, scholars and students, Google and the Digital Divide: The Biases of Online Knowledge provides invaluable insight into the significant role that search engines play in growing the digital divide between individuals, organizations, and states. With a specific focus on Google, author Elad Segev explains the concept of the digital divide and the effects that today's online environment has on knowledge bias, power, and control. Using innovative methods and research approaches, Segev compares the popular search queries in Google and Yahoo in the United States and other countries and analyzes the various biases in Google News and Google Earth. Google and the Digital Divide shows the many ways in which users manipulate Google's information across different countries, as well as dataset and classification systems, economic and political value indexes, specific search indexes, locality of use indexes, and much more. Segev presents important new social and political perspectives to illustrate the challenges brought about by search engines, and explains the resultant political, communicative, commercial, and international implications.
Power, communication and the internet -- The structure and power of search engines -- Google and the politics of online searching -- Users and uses of Google's information -- Mass media channels and the world of Google News -- Google's global mapping.
Includes bibliographical references (pages 191-218) and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2014. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Google (Firm); Search engines; Internet searching; Electronic books